MANAGEMENT OF ACUTE PROMYELOCYTIC LEUKEMIA IN THE ELDERLY - Francesco Lococo; Roberto Latagliata; Massimo Breccia (Mediterranean Journal of Hematology and Infectious Diseases)
Unlike other forms of AML, APL is less frequently diagnosed in the elderly and has a relatively favourable outcome. Elderly patients with APL seem at least as responsive to therapy as do younger patients, but rates of response and survival are lower in this age setting owing to a higher incidence of early deaths and deaths in remission when conventional treatment with ATRA and chemotherapy is used. Elderly APL patients are more likely to present with low-risk features compared with younger patients, and this may explain the relative low risk of relapse reported in several clinical studies. Alternative approaches, such as arsenic trioxide and gentuzumab ozogamicin have been tested with success in this setting and could replace in the near future frontline conventional chemotherapy and ATRA.